Tone at the Top: An Ethics Code for Directors? - Schwartz, Mark S. (Journal of business ethics, 2005)
Recent corporate scandals have focused the attention of a broad set of constituencies on reforming corporate governance. Boards of directors play a leading role in corporate governance and any significant reforms must encompass their role. To date, most reform proposals have targeted the legal, rather than the ethical obligations of directors. Legal reforms without proper attention to ethical obligations will likely prove ineffectual. The ethical role of directors is critical. Directors have overall responsibility for the ethics and compliance programs of the corporation. The tone at the top that they set by example and action is central to the overall ethical environment of their firms. This role is reinforced by their legal responsibilities to provide oversight of the financial performance of the firm. Underlying this analysis is the critical assumption that ethical behavior, especially on the part of corporate leaders, leads to the best long-term interests of the corporation. We describe key components of a framework for a code of ethics for corporate boards and individual directors. The proposed code framework is based on six universal core ethical values: (1) honesty; (2) integrity; (3) loyalty; (4) responsibility; (5) fairness; and (6) citizenship. The paper concludes by suggesting critical issues that need to be dealt with in firm-based codes of ethics for directors.